Exploring financial exploitation of older persons in family setting - Che Amani @ Mohd Kamal, Nurfadhilah; Kahar, Rojanah; Ibrahim, Rahimah; Hasbullah @ Abdullah, Muslihah (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
The main purpose of this study is to explore the experience on financial exploitation of older person by family members. This include to discover the meaning of financial exploitation among older persons as victim of financial exploitation and to explore the lived experience of financial exploitation incidents among older persons. Phenomenological approach is chosen to answer this the research question and using maximum and snowballing sampling, this study will employ in depth interview as method for collecting data This study will give weightage to the views of older persons through in-depth interview as the main instrument for data collection. The participants sampling in the study comprise of those older persons in community dwelling and institutionalised setting in Selangor. The findings of this study will be helpful for researchers to understand financial exploitation of older person’s phenomenon from the perspectives of older Malaysians. This study may contribute to the body of knowledge in discovering the experience and identifying the potential barriers that the older persons themselves face in detecting and disclosing financial exploitation in family setting in Malaysian context.